PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP MINAT BELI ULANG PELANGGAN PT SAKYO PUTRA PRATAMA - Dwi Anggraeni; Amanda Setiorini (Jurnal Ekonomi dan Industri, 2021)
This study aims to identify the effect of service quality and price on the repurchase of merchandise at PT Sakyo Putra Pratama, using quantitative descriptive research. The analytical method used is multiple linear regression analysis. The results showed that service quality and price simultaneously have a positive and direct impact to repurchasing the merchandise. The calculation of the correlation coefficient and determination coefficient indicate that there is a very close level of relationship between the variabels of service quality and price towards repurchasing at PT Sakyo Putra Pratama.